THE INFLUENCE OF STORE ATMOSPHERE, PRODUCT QUALITY AND PRODUCT VARIANTS ON CUSTOMER SATISFACTION AT DANKE CAFÉ SINGARAJA - Ni Wayan Novi Budiasni; Gede Tista Widiartana (ARTHA SATYA DHARMA, 2023)
This study aims to determine the effect of store atmosphere, product quality and product variants on customer satisfaction at Danke Café Singaraja. The sample in this research is 75 people. The data collection techniques in this study used questionnaires and documentation. The analysis technique used in this research is validity and reliability test, classic assumption test, multiple linear regression analysis, coefficient of determination test, t-test, f-test. Research results show thatIn accordance with the test results show that the store atmosphere variable has a positive regression coefficient value which has a positive and significant effect on customer satisfaction. In accordance with the test results show that the product quality variable has a positive regression coefficient value which has a positive and significant effect on customer satisfaction. In accordance with the test results show that the product variables have positive regression coefficient values ​​that have a positive and significant effect on customer satisfaction.